Terrorism and its Impact on Domestic Women: A Case Study of Peshawar (2005-2020) - Samia Hassan; Ali Hassnain (Journal for Social Science Archives, 2025)
Terrorism has a detrimental impact on the social structure and economic stability of countries, with particularly vulnerable groups like domestic women facing severe repercussions. This research paper investigates the diverse effects of terrorism on domestic women in Peshawar, Pakistan, between 2005 and 2020. Utilizing qualitative research techniques, such as interviews and analysis of secondary data, the study reveals the psychological trauma, economic vulnerability, social disruption, and limited access to vital services that these women endure. The results show increased psychological distress, financial difficulties resulting from the loss of male family members, disruption of support networks, and educational challenges. The paper emphasizes the need for gender-sensitive policy measures aimed at providing psychosocial support, promoting economic empowerment, and addressing gender norms to build resilience and inclusivity. This research enhances the understanding of gendered aspects of conflict and underscores the importance of incorporating women’s experiences in counterterrorism and rebuilding initiatives (Hassan, 2024).